2009
DOI: 10.1245/s10434-009-0778-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Response to Decongestive Therapy in Patients with Breast-Cancer-Related Lymphedema

Abstract: This study shows that compliance to bandages during CDT is one of the most important predictors of response. Moreover, data support the idea that more severe lymphedemas have a worse response to treatment, and it should be recommended in early stages. The association between the season of treatment and response was also very strong, so weather conditions are an additional factor that must be taken into account in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 32 publications
4
45
2
1
Order By: Relevance
“…Vignes et al [12] found that the chronicity of www.e-arm.org lymphedema was a predictive factor of response when the response was measured in the absolute value of reduction in lymphedema volume; but relative percentage of volume-reduction was same, regardless of the chronicity. Moreover, in many other studies, the chronicity of lymphedema was not a predictive factor of response [11,14,15,29,30]. Based on these studies, there seems to be a low-correlation between the chronicity and CDT outcome.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Vignes et al [12] found that the chronicity of www.e-arm.org lymphedema was a predictive factor of response when the response was measured in the absolute value of reduction in lymphedema volume; but relative percentage of volume-reduction was same, regardless of the chronicity. Moreover, in many other studies, the chronicity of lymphedema was not a predictive factor of response [11,14,15,29,30]. Based on these studies, there seems to be a low-correlation between the chronicity and CDT outcome.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies [11,12,14,33] have not assessed the presence of fibrosis, and an explanation for the relationship between fibrosis and CDT response cannot be found. Although there is a study [15] which www.e-arm.org reported that fibrosis is not a predictive factor of CDT response, the study does not specify methods of measuring fibrosis. Therefore, further study is required to validate the qualitative evaluation of tissue character and skin condition with additional instruments, such as ultrasound, tissue tonometer, and bioimpedance.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,19 Secondary thresholds of two standard deviations were also determined. 20 Intra-rater reliability and normal fluctuation of BIS ratios were determined with intraclass correlation coefficients (ICC (1,1) ) from data collected on two occasions seven days apart. Standard error of the measurement (SEM = SD 1st test O1-ICC) and minimal detectable change (MDC = 1.96 O2 SEM) were determined for each arm segment and the hand.…”
Section: Discussionmentioning
confidence: 99%
“…Intraclass correlation coefficients (ICC (1,1) ) assessed the test-retest (intra-rater) reliability of hand and segmental BIS ratios measured 1 week apart for 20 women without breast cancer and four women with stable lymphedema. The intra-rater reliability of the BIS ratio for the hand and four limb segments was very high (ICC (1,1) range 0.95 and 0.98; Table 4).…”
Section: Reliability Of Bis Ratios For Segments and Handmentioning
confidence: 99%
“…It can lead to pain and a sensation of heaviness in the affected area. These symptoms can affect physical functions and also cause psychological distress4 ) . Consequently, it decreases the patient’s quality of life.…”
Section: Introductionmentioning
confidence: 99%